Integrating Sustainability, Digitalization, and Strategic Alliances in B2B Relationship Marketing: A Systematic Literature Review of The Port Sector - Rosita Septiani; Herri Herri; Donard Games; Syafrizal Syafrizal (Riviera Publishing, 2026)
The maritime and port industry has undergone rapid transformation driven by sustainability pressures, digital disruption, and increasing global competition, requiring the reconfiguration of traditional Business-to-Business (B2B) relationship marketing practices. This study examined the evolution of B2B relationship marketing within the maritime and port sector through a Systematic Literature Review (SLR) using the PRISMA framework. From an initial pool of 180 Scopus-indexed publications, 46 articles published between 2015 and 2025 met the inclusion criteria and were thematically synthesized. The review identified three interconnected dimensions shaping contemporary port-related B2B marketing: sustainability, digital innovation, and port performance. Sustainability has shifted from a peripheral operational concern to a strategic priority, as reflected in green port initiatives, ecological governance, and decarbonization commitments. Simultaneously, digital technologies, including artificial intelligence, blockchain, and predictive analytics, have transformed operational efficiency while enabling more sustainable and resilient business practices. Port performance, traditionally measured through productivity and cost efficiency, is increasingly evaluated based on technological capabilities, environmental responsibility, and collaborative value creation. The findings further revealed that strategic partnerships play a pivotal role in connecting digital transformation with sustainability objectives, thereby strengthening competitiveness and long-term resilience within the port ecosystem. Conceptually, this review highlighted the growing integration of relationship marketing, digitalization, and sustainability-oriented strategic management in maritime logistics. Nevertheless, several research gaps remain, including limited qualitative investigations, insufficient geographical diversity, and inadequate attention to circular economy practices and digital literacy capabilities. Addressing these limitations requires methodological diversification and broader contextual exploration to better understand how ports can maintain competitive B2B relationships in an increasingly digital and sustainability-driven environment.